Developing New Translation Profiles for an Undergraduate Program - Gabriel Quiroz (Lenguaje, 2011)
In this article, new translators’ profiles are discussed based on the development of two competences in an undergraduate program: the extralinguistic competence, and the instrumental and professional competence, e.g., specialized knowledge, the knowledge and use of modern technologies, and the knowledge of the market. This article focuses on the importance of developing these two subcompetences in translation programs in order to produce competitive professional translators, and it proposes a set of recommended activities for the development of each subcompetence. Likewise, the advantages and disadvantages of these activities are discussed as well as the changes and implications for translation teaching.